Identification of a Distinct Small Cell Population from Human Bone Marrow Reveals Its Multipotency In Vivo and In Vitro - Wang, James (Public Library of Science, 2014)

(untitled)
Small stem cells, such as spore-like cells, blastomere-like stem cells (BLSCs), and very-small embryonic-like stem cells (VSELs) have been described in recent studies, although their multipotency in human tissues has not yet been confirmed. Here, we report the discovery of adult multipotent stem cells derived from human bone marrow, which we call StemBios (SB) cells. These isolated SB cells are smaller than 6 ìm and are DAPI+ and Lgr5+ (Leucine-Rich Repeat Containing G Protein-Coupled Receptor 5). Because Lgr5 has been characterized as a stem cell marker in the intestine, we hypothesized that SB cells may have a similar function. In vivo cell tracking assays confirmed that SB cells give rise to three types of cells, and in vitro studies demonstrated that SB cells cultured in proprietary media are able to grow to 6–25 ìm in size. Once the SB cells have attached to the wells, they differentiate into different cell lineages upon exposure to specific differentiation media. We are the first to demonstrate that stem cells smaller than 6 ìm can differentiate both in vivo and in vitro. In the future, we hope that SB cells will be used therapeutically to cure degenerative diseases.